2015
DOI: 10.1242/dev.126995
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of Eclosion hormone action during Drosophila larval ecdysis

Abstract: Insect growth is punctuated by molts, during which the animal produces a new exoskeleton. The molt culminates in ecdysis, an ordered sequence of behaviors that causes the old cuticle to be shed. This sequence is activated by Ecdysis triggering hormone (ETH), which acts on the CNS to activate neurons that produce neuropeptides implicated in ecdysis, including Eclosion hormone (EH), Crustacean cardioactive peptide (CCAP) and Bursicon. Despite more than 40 years of research on ecdysis, our understanding of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…By targeting a calcium-sensitive GFP (GCaMP) to different peptidergic ensembles, Kim et al (2006) showed that each of these sets of peptidergic neurons is activated at a particular time and for a specific duration following a challenge by ETH in vitro. By correlating these times with the expression of the different behavioral phases of ecdysis, each set was assigned a role in the control of particular ecdysial subroutine, which was also broadly consistent with functional and genetic evidence (Diao et al, 2016; Kim et al, 2006, 2015; Krüger et al, 2015; Lahr et al, 2012; Park et al, 2003). Nevertheless, the mechanisms by which the direct targets of ETH would be activated at different times after an ETH challenge remained unanswered.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…By targeting a calcium-sensitive GFP (GCaMP) to different peptidergic ensembles, Kim et al (2006) showed that each of these sets of peptidergic neurons is activated at a particular time and for a specific duration following a challenge by ETH in vitro. By correlating these times with the expression of the different behavioral phases of ecdysis, each set was assigned a role in the control of particular ecdysial subroutine, which was also broadly consistent with functional and genetic evidence (Diao et al, 2016; Kim et al, 2006, 2015; Krüger et al, 2015; Lahr et al, 2012; Park et al, 2003). Nevertheless, the mechanisms by which the direct targets of ETH would be activated at different times after an ETH challenge remained unanswered.…”
Section: Resultsmentioning
confidence: 69%
“…Eclosion hormone (EH) is a key neuropeptide in the control of ecdysis (Ewer and Reynolds, 2002; Gammie and Truman, 1999; Krüger et al, 2015). It is involved in potentiating and accelerating the release of ETH that causes the sudden onset of ecdysis behaviors (Ewer et al, 1997; Kingan et al, 1997); in addition, it plays a critical role within the CNS for the expression of ecdysis behaviors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 ETH is a peptide that activates neurons that produce the eclosion hormone (EH), CCAP and bursicon. 18 Other important neuropeptides involved in growth and development are the insulin like peptides (ILP´s), orcokinins and allatostatins. ILP´s seem to be involved in development, regulation of carbohydrate and lipid metabolism, 19 diapause induction, 20 stress resistance, 21 regulation of sexual behaviors, 22 regulation of life span 23 and regulation of sleep.…”
Section: Anopheles Albimanus Neuropeptides During Developmentmentioning
confidence: 99%